2020
DOI: 10.3390/agronomy10040580
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cover Crops on the Biodiversity and Abundance of Ground-Dwelling Arthropods in a Mediterranean Pear Orchard

Abstract: The intensification of agriculture has led to the reduction of the diversity of arthropods in agroecosystems, including that of ground-dwelling species. The aim of our work was to assess the effect of a sown cover crop on the diversity of ground-dwelling arthropods, including key predators for pest control in pear orchards. The trial was carried out in a pear orchard divided in three blocks; two treatments (cover-cropping and control) were implemented in each block. A seed mixture of 10 plant species was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 86 publications
2
17
0
1
Order By: Relevance
“…Consistent with previous studies [31,57,75], our study showed that cover crops support greater species richness and diversity of ground beetles than winter wheat, which could have positive effects on weed seed and insect pest regulations. Interestingly, as opposed to the effects shown by cropping systems, the ground beetle communities were different between crop phases during the initial two years of this study, but they were similar during the final three years.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies [31,57,75], our study showed that cover crops support greater species richness and diversity of ground beetles than winter wheat, which could have positive effects on weed seed and insect pest regulations. Interestingly, as opposed to the effects shown by cropping systems, the ground beetle communities were different between crop phases during the initial two years of this study, but they were similar during the final three years.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, one of the additional benefits of cover crops may be promoting biodiversity including the diversity of economically insignificant species (Nicholls & Altieri 2013;Li et al, 2016;de Pedro et al, 2020), and thus they can be of high conservation interest.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one of the additional benefits of cover crops may be promoting biodiversity including the diversity of economically insignificant species (Nicholls & Altieri 2013; Li et al , 2016; de Pedro et al , 2020), and thus they can be of high conservation interest. Theoretically, since cover crops are a more heterogeneous ecosystem with available niches (Rosenzweig, 1995; Dufour et al , 2006), they should support more species.…”
Section: Discussionmentioning
confidence: 99%
“…In cover crop management, a mix of herbaceous plants or flowering plants is often used to house natural enemies in orchards (Eric, 1995;Marliac et al, 2016;de Pedro et al, 2020). For example, it is suggested that perennial flower strips should be placed in orchards to maintain natural enemies (Cahenzli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%